Analysis of Prospective Physics Teachers’ Ability to Design Experiments in University of West Sulawesi - Mutmainna Mutmainna (Universitas Pendidikan Mandalika, 2021)
Physics learning is identified to hand-on activities and built through scientific activities. Identification of students' understanding regarding physics theories and the ability to design physics experiments was allegedly very important to support the output profile of Physics Education Study Program in the form of professional educators. This study aimed to determine (1) the profile of prospective physics teacher's ability to design experiments at the University of West Sulawesi; (2) the category of prospective physics teacher's ability to design experiments; and (3) learning evaluation of Design and Analysis course of Secondary School Physics Practicum. This research is a descriptive exploratory study, where data is collected using an open-ended observation sheet with seven aspects of the ability to design experiment. Descriptive statistics were used to analyze research data obtained from 40 research subjects. The results showed that (1) overall, the prospective physics teacher's ability to design experiments was in the range 1.96 - 2.51; (2) the prospective physics teacher's ability to design experiments at the University of West Sulawesi was in the quite good and very good categories; (3) the presentation skill was an aspect that needs to be improved, while the theoretical basis understanding was the most prominent aspect based on the learning evaluation results of Design and Analysis course of Secondary School Physics Practicum